Analisis Penerapan Prinsip Good Corporate Governance Pada Penggunaan Dana Bantuan Operasional Sekolah - Rosydah, Faizatur; Ningtiyas, Nabilah Wahyu; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
With the application of the principles of good governance, the goal is to manage BOS funds in a way that meets their requirements. This is a critical requirement. The relationship mechanism between the various parties who manage the company as well as the